Advances in Pediatric Surgery Simulation-Based Training - Laquanda T. Knowlin; Nicholas M. B. Laskay; Nehemie P. Jules; Jakub Godzik; Todd P. Chang; Ryan G. Spurrier (MDPI AG, 2023)
Pediatric surgery is the diagnostic, operative, and postoperative surgical care of children with congenital and acquired anomalies and diseases. The early history of the specialty followed the classic "see one, do one, teach one" philosophy of training but has since evolved to modern methods including simulation-based training (SBT). Current trainees in pediatric surgery face numerous challenges, such as the decreasing incidence of congenital disease and reduced work hours. SBT consists of several modalities that together assist in the acquisition of technical skills and improve performance in the operating room. SBT has evolved to incorporate simulator models and video gaming technology, in parallel with the development of simulation in other surgical and non-surgical pediatric fields. SBT has advanced to a level of sophistication that means that it can improve the skills of not only pediatric surgery trainees but also practicing attending surgeons. In this review, we will discuss the history of pediatric surgery, simulation in pediatric surgery training, and the potential direction of pediatric surgical simulation training in the future.